2006
DOI: 10.1292/jvms.68.1219
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Analysis of Hepatic T Lymphocytes in a Dog with Chronic Hepatitis

Abstract: ABSTRACT. We evaluated hepatic T lymphocyte phenotypes in a dog with chronic hepatitis. Before treatment, numerous CD3+ lymphocytes were demonstrated in the liver, and the ratio of CD4+/CD8+ was remarkably high (2.96; reference range, 0.33 ± 0.12). After treatment, CD3+ lymphocyte infiltration in the liver was reduced, and the ratio of CD4+/CD8+ decreased to 0.31. Therefore, hepatic T lymphocytes, especially CD4+ lymphocytes, might play a central role in the pathogenesis of this dog with chronic hepatitis. KEY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Corticosteroids were used in all cases. It is uncertain if this may have influenced their survival considerably, although the possible beneficial effect of this drug on Cocker Spaniel hepatitis has been reported , . Corticosteroids have been reported to have a direct or indirect (ie, via suppression of the inflammation) antifibrotic effect .…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids were used in all cases. It is uncertain if this may have influenced their survival considerably, although the possible beneficial effect of this drug on Cocker Spaniel hepatitis has been reported , . Corticosteroids have been reported to have a direct or indirect (ie, via suppression of the inflammation) antifibrotic effect .…”
Section: Discussionmentioning
confidence: 99%
“…Specific criteria for the diagnosis of immune‐mediated hepatitis in dogs have not been developed. An immune basis in some dogs with idiopathic CH is suggested by several criteria (Table ) which include the presence of lymphocytic infiltrates in the liver, abnormal expression of major histocompatibility complex class II proteins, positive serum autoantibodies, familial history of liver disease, association with other immune‐mediated disorders, female predisposition, and favorable response to immunosuppression . A presumptive clinical diagnosis of immune‐mediated CH in the dog requires elimination of other etiologies and a favorable response to immunosuppressive treatment.…”
Section: Etiologymentioning
confidence: 99%
“…The overall mean age when clinical signs are reported is 7.2 years (11 studies, n = 983 dogs). Disease duration before diagnosis is unclear . Reported age ranges in specific breeds are shown in Supporting Information Table S1.…”
Section: Signalment and Clinical Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between chronic hepatitis and an immune-mediated process has also been suggested in a study in which in the liver of a dog affected by chronic hepatitis was found an increased ratio of CD4+/CD8+ lymphocytes (33), and in a study in dogs with chronic hepatitis showing proliferation of peripheral blood mononuclear cells in response to liver membrane antigens (34). Furthermore, a study performed on Dobermans affected by hepatitis at different clinical stages, showed upregulation of MHC class II antigens in hepatocytes, leading the authors to hypothesize an autoimmune ground (35), similarly to another study in which for Doberman hepatitis, showing an association between the disease and the homozygous haplotype DLA-DRB1*00601/DQA1*00401/DQB1*01303, it has been hypothesized an immune origin (36).…”
Section: A B C Dmentioning
confidence: 73%